Auditors' Perception on Ethical Responsibility in Auditing: A Qualitative Study - Wijaya, Ari; Suryani, Bella; Pratama, Cindy; Permadi, Dito; Putri, Eka (Manunggal Halim Jaya, 2021)
This qualitative study explores auditors' perceptions of ethical responsibility in auditing, aiming to elucidate the multifaceted dynamics shaping their attitudes and behaviors. The research delves into various dimensions of ethical behavior, organizational factors, professional standards, and regulatory frameworks influencing auditors' conduct. Through thematic analysis of existing literature, key concepts related to ethical responsibility in auditing are defined, and specific aspects pertinent to the research context are elucidated. The study highlights the critical role of ethical behavior in maintaining public trust and confidence in financial reporting, emphasizing principles of integrity, objectivity, independence, and professional competence. Organizational culture, professional norms, and regulatory oversight mechanisms are identified as influential factors shaping auditors' ethical decisions and actions. Moreover, the research underscores the importance of professional skepticism and independence as essential components of auditors' ethical responsibility, emphasizing their role in enhancing audit quality and deterring financial misconduct. The findings contribute to theoretical discourse on auditing ethics, enriching our understanding of the ethical imperatives governing auditors' conduct. Furthermore, practical implications for auditing firms, regulatory bodies, and professional associations are discussed, with recommendations for promoting ethical conduct and integrity within the profession.